Natural and processed milk and oil body emulsions: Bioavailability, bioaccessibility and functionality. (July 2017) - Gallier, Sophie; Acton, Dennis; Garg, Manohar; Singh, Harjinder
Abstract: A well-studied naturally-occurring lipid structure is the oil-in-water emulsion droplet. The interfacial quality and quantity of the oil droplets play a key role in the digestion in the gut and subsequent lipid uptake and may have longer term health consequences. Studies on natural droplets, the milk fat globules and the oil bodies, and the effect of processing on their structure and on their digestion are discussed. This article reviews how processing affects the structure of naturally-occurring oil droplets, how it impacts the lipid bioavailability and bioaccessibility, and highlights recent developments to mimic natural lipid emulsion functionality for infant nutrition.